English teachers’ awareness of using ICT in primary school of Shenzhen city in China - Li, L.; Hoque, K.E.; Othman, A.J.; Razak, Ahmad Zabidi Abdul (Macrothink Institute, 2014)
The study aims to assess the current situation concerning the use of ICT in Shenzhen city of China. This study was a survey using a set of questionnaire to investigate ICT as a tool in English teaching procedure in primary school in Shenzhen city. Data were collected from 172 teachers teaching English in primary schools. Data revealed that 61.0% of English teachers in primary schools of the respondents in Shenzhen have Bachelor Degrees, 29.1% have Diplomas and 3.5% have got the Master Degree. There were 63.9% of teachers in the respondent were using English during their English class. There were 91% of respondents agree with that their principals had already informed them the ICT policies. More than 80.0% teachers strongly agreed that the ICT policies implementing in schools really helped their teaching. The findings have revealed the degree of teachers’ awareness of ICT policy that can be considered as feedback to policy makers and implementers.